Analisis Semiotika Realita Kemiskinan dalam Film Parasite Karya Sutradara Bong Jon Hoo - Arifin, Bustanul (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2023)
The research entitled "Semiotic Analysis of the Reality of Poverty in the film Parasite by director Boong Jon Hoo" is qualitative research. Semiotics is the study of signs, the functioning of signs and the production of meaning. The purpose of this research study was to find out the description of the reality of poverty contained in the film Parasite. The researcher chose 12 scenes and analyzed them using semiotics from expert Charles Sanders Peirce which were classified into three parts, namely icons, indexes and symbols. The results of the study show that there are many scenes that contain elements of the reality of poverty including simple, free, dirty, the job of folding pizza boxes, used goods, smelly, dirty, valuables, no money. The number of scenes that show the reality of poverty in the film Parasite, researchers as viewers see that poverty does not only come from individual factors but there are other factors that cannot be separated